A Corpus of Critical Citations Contexts - Bordignon, Frédérique; Gambette, Philippe (Journal of Open Humanities Data, 2024)
We present here a corpus of 505 critical citation contexts, i.e. a set of sentences or propositions that contain at least one citation of a study towards which the author(s) has/have a negative opinion. Those contexts come from other existing annotated corpora, from our readings about critical citation and disagreement in science, and from contexts manually annotated by native speakers of English. We have re-annotated all those contexts in order to be sure that they match our definition of critical citations. This corpus can be helpful to train tools dedicated to the automatic retrieval of critical citations.